The Influence of Perceived Value on Repurchase Intention Through Customer Satisfaction in Specialty Food Tourism - Syahla Karima Musfha; Widi Widya Mukti; Dewi Turgarini; Caria Ningsih (Universitas Sebelas Maret, 2025)
The specialty food tourism sector has experienced significant growth, yet the mechanism through which perceived value drives customer loyalty in artisanal food businesses remains insufficiently understood. While prior research has established links between perceived value, satisfaction, and behavioral intentions, few studies have examined these relationships specifically within the specialty food tourism context. This study investigates the influence of perceived value on repurchase intention through customer satisfaction in the context of Whimsical Cookies, a specialty food tourism business. Using a quantitative approach with 150 respondents selected through purposive sampling, data were analyzed with SPSS 25 through hierarchical multiple regression. The findings reveal that perceived value significantly affects repurchase intention directly (β = 0.621, p < 0.001). The mediating role of customer satisfaction was further confirmed through the Sobel test, which verified the significance of the indirect effect (β = 0.356 for perceived value and β = 0.361 for customer satisfaction, both p < 0.001), with the mediation model explaining 41.7% of the variance in repurchase intention (R² = 0.417), indicating that satisfaction functions as a partial mediator rather than merely improving explanatory power. Practically, specialty food businesses can strengthen repurchase behavior by enhancing experiential value through artisanal presentation, authentic storytelling, and distinctive packaging, while sustaining satisfaction through consistent service quality and active monitoring of customer feedback.Keywords: artisanal culinary business; behavioral loyalty; consumer value perception; experiential marketing; mediation analysis; tourist purchasing behavior